Relationship between Parental Social Support and o Menarche Readiness among Adolescents at Islamic Centre Binbaz: A Cross-sectional Study - Widyaningrum, Rahmah; Raditya, Ngaisah Eka; Anggraeni, Dwi Nur; Antari, Isti (STIKep PPNI Jawa Barat, 2024)
Aims: This study aims to analyze the relationship between the social support of parents and the preparedness for menarche in adolescents. Methods: This research uses quantitative research with a cross-sectional design. The study was conducted at the Islamic Centre Binbaz Elementary High School. The sample consisted of 50 respondents using the total sampling techniques. The instruments used were the social support questionnaire of parents and the preparedness for menarche. Bivariate analysis used the Spearman rho test. Result: Parental support for menstruation in the negative category of 31 people (62%) and preparedness for menarche in female adolescents is as high as 35 people (70%). There is a relationship between social support of parents with menarche readiness with a p-value of 0.024 and a correlation coefficient (r) of 0.320. Discussions: In reproductive health, especially regarding menarche, parents are expected to communicate better with their children about puberty issues, because it helps ensure healthy child sexuality. Focusing on building communication between parents and children, is an effective strategy for increasing overall support for children's health. Parental support in preparing children for menarche includes being an educator who provides complete and correct information about menstruation, maintaining hygiene during menstruation, and both physical and mental support when facing menarche. Conclusion: This research indicates a relationship between parental social support and readiness for menarche in adolescents, with a weak correlation level and a positive correlation. This means that adolescents who have high parental support have a higher preparedness for menarche.